Analytical behavior of carbon steel-concrete-stainless steel double-skin tube (DST) used in submarine pipeline structure. (January 2019) - Wang, Fa-Cheng; Han, Lin-Hai
Abstract: One type of submarine composite pipeline structure, with carbon steel-concrete-stainless steel (CCS) double-skin tube (DST), was introduced in this paper. This composite pipeline was expected to make optimal use of the three types of the materials, and provide significant structural and internal corrosion resistance. This study investigated the compressive and flexural behavior of the composite pipeline under internal content pressure and external hydrostatic pressure through finite element analysis (FEA). Finite element models were developed, where non-linear material properties of stainless steel and composite actions between constituent parts were considered. The models were verified through the comparisons between the numerically and experimentally determined results, in terms of load-deformation histories, failure modes and ultimate strength. Structural behaviors of the composite pipeline under pressures were compared with those without content and hydrostatic pressure. Parametric studies were carried out to investigate the effects of the outer carbon steel strength, inner stainless steel strength, concrete strength and hollow ratio on the compressive and flexural behaviors of the composite pipelines subjected to pressures. Highlights: Carbon steel-concrete-stainless (CCS) submarine composite pipeline was proposed and the corresponding FE models were developed. Structural behavior of CCS DST used in submarine pipeline under pressures, compression and bending were analyzed. The parametric studies were conducted on the CCS submarine composite pipeline.